Perbandingan Kondisi Kemampuan Awal dan Akhir Peserta Pelatihan Realistics Mathematics Education Smart Camp 2021 - Farida Nursyahidah; Irkham Ulil Albab; Muhtarom Muhtarom; Arif Wibisono (Perkumpulan Kualitama Edukatika Indonesia, 2022)
Learning mathematics using traditional setting make students only memorize formulas and are good at counting without knowing the meaning behind the formula or calculation. As a result they cannot use mathematics in problem solving. Good quality in learning mathematics can only be realized by teachers who master the right mathematical approach. Realistic Mathematics Education Smart Camp is a 32 hours model training activity to facilitate mathematics teachers who are members of the city/district Mathematics council to improve the quality of mathematics learning through training in making progressive learning designs through the RME approach. This article compares how the condition of teachers related to their mathematical abilities in solving problems before and after participating in the training. Mathematics teacher show that their ablity in beginning were still lay on third level Bloom Cognitive hierarchy. They master calculating and applying formula in certain mathematics application. However, in the real context, they failed to use mathematics. After given progressive workshop, they were able to apply mathematics in any condition. They literated in using mathematics to solve daily problem. From this comparison, it can be concluded that the RME Smart Camp training has a significant role in improving the ability of teachers to prepare mathematics lessons that foster meaningful understanding using students' abilities.